Regulation and Mechanism of miR-518d through the PPARα-Mediated NF-κB Pathway in the Development of Gestational Diabetes Mellitus - Hui Qiu; Xuemin Liu; Shenshen Yao; Jiaren Zhou; Xue Zhang; Juan Du (Journal of Diabetes Research)
Objectives. To observe the role of miR-518d in pregnant women with gestational diabetes mellitus (GDM) and its adjusting effects on PPARα and to explore the regulatory mechanisms of the NF-κB pathway in the development and progression of GDM. Methods. Placenta tissues and peripheral plasma were obtained from pregnant women with normal pregnancy and GDM, respectively, followed by the detections of miR-518d contents by RT-PCR and the expression levels of inflammatory factors using ELISA. Human placenta trophoblast cells (HTR8/SVneo) were cultured under the conditions of physiological glucose (PG group) and high glucose level (HG group). Cells in the HG group were transfected with miR-518d control, mimics, and inhibitors and were separately administered with a PPARα-specific antagonist (GW6471) and PPARα siRNA, and cells were divided into the following groups: HG+miR-518d control group (HGNC group), HG+miR-518d mimic group (HGM group), HG+miR-518d inhibitor group (HGI group), HGI+PPARα antagonist group, and HGI+PPARα siRNA group. The relative expression levels of miR-518d, PPARα, and its downstream genes and NF-κB signalling pathway-related genes were detected by RT-PCR and Western blotting. The contents of inflammatory factors were examined by Western blotting. A dual-luciferase report assay was performed to validate the correlations between miR-518d and PPARα. In this study, mouse GDM models were established to further prove the previous hypothesis with an in vivo experiment. A total of 40 C57BL/6J mice were randomly divided into the following groups: normal diet group (ControlMs), GDM group (GDMMs group), GDM+miR-518d antagomir group, and GDM+miR-518d antagomir+PPARα antagonist group. The mouse model of GDM was established by feeding with combined high-sugar and high-saturated fat diet and injecting streptozotocin (STZ) after 15-day feeding. Female and male mice were cocaged in the number ratio of 2 : 1, and the evidence of vaginal suppository detected in female mice was marked as D0 of pregnancy. The contents of total cholesterol (CH), triglyceride (TG), fast glucose, and insulin (INS) were examined using ELISA, followed by the evaluation of insulin resistance (IR). The related expression levels were also detected with the above methods shown in the previous cell culture. Results. miR-518d has a high expression level in placentas with GDM. As the target gene of miR-518d, PPARα was downregulated with the increased levels of miR-518d. When GDM occurs, inflammatory responses were elevated, stimulating the nuclear transport process of NF-κB. Activated NF-κB triggered the phosphorylation of IKKβ and IκBα. Conclusions. High expression of miR-518d was observed in the development of GDM. In this study, we validated that miR-518d negatively regulates the expression of PPARα and triggers the nuclear transport process of NF-κB and phosphorylation of pathway-associated proteins leading to an inflammatory response and the development of GDM.